Issues in determining the real value of concession fees when granting concession for commercial use of maritime domain - Mezak, Vlado (Array, 2019)
This paper analyzes the legislation related to concessions on maritime domains and indicates the need to adjust certain legal provisions to improve the quality of the concession granting procedure. The object of this paper is to indicate the issues in determining the real value of a concession fee in the process of preparing a feasibility study for granting the concession, and to give a scientific contribution by proposing procedures and measures, which can enable setting more precise concession fee values. Using the methods of comparison, analysis, and synthesis, authors prove that in the process of preparing a feasibility study for granting the concession it is not possible to assess the real value of the concession and concession fee with certainty, as it is necessary to estimate economic sizes in the long term. Each concession contract, lasting longer than five years, should be subject to a peer review owing to changes in economic, political, demographic, and other indicators, and if necessary, the value of concession fee should be adjusted accordingly. The authors explain the stated imprecision in the estimate of economic indicators by the index of uncertainty of economic policies, and with the inability of long-term forecasting of potential economic crises.